Uncertainty Analysis of Squeeze-Type Regulation Method for Equal Expulsion of Parallel Tanks. (August 2019) - Yin, W J; Lin, Z; Wang, M J
Abstract: Focused on the problem of unbalanced propellant consumption in parallel tanks of propulsion system, a squeeze-type regulation method based on the gas law method was discussed in the paper. Taking the tank system as the research object, the thermodynamic models under isothermal, adiabatic and other conditions were given and the factors affecting the uncertainty of the model were analysed. The results show that the measurement uncertainty of the model mainly comes from the pressure measurement accuracy and the volume measurement accuracy. The model was applied to different cases and the influence law of different tank parameters on the model uncertainty was studied. It is found that under the premise of the fixed pressure difference of the parallel tanks, the uncertainty of the regulation model is almost linear with the regulation amount. In addition, the relative uncertainty of the model can be reduced effectively by improving the pressure difference of the parallel tanks. The accuracy of the regulation model can reach to 7.7%, which can meet the requirements for on-orbit use.